Artificial Intelligence: Counselling Buddy Minimo - Mohamad Zamin Nizam, Auni (IRC, 2019)
Minimo is a counselling companion for all ages. The stigma of having mental illness scares them as they think that no one is there to listen to their concern. This fear will lead them to suffer their whole life without proper treatment and can lead to suicidal attempt. Minimo is there to become your listening ear and become your buddy. The methodology use for this project is RAD methodology very emphasize on working software and user feedback over a strict planning and requirements that has been gathered. RAD requires the prototype to develop as soon as the requirement has been gathered up until the prototype is ready to become the finished product. The users are the ones that will always give the feedbacks on the prototype. Thus, in building Minimo, a design survey will be given out to the public. The objective is to obtain as many feedbacks as possible to improve the proposed design of Minimo.